Morisco Women, Written Texts, and the Valencia Inquisition - Surtz, Ronald E. (The sixteenth century journal, 2001)
The Spanish Moriscos, while nominally Christian, attempted to retain the Islamic identity of their forefathers, even in the face of inquisitorial persecution. Morisco men had different relationships to forbidden texts in Arabic than women did. When the officials of the Inquisition arrived to search their homes, men were seldom inclined to defend their books against seizure and, if anything, resorted to attempting to bribe the inquisitorial constables. In contrast, women went to great lengths to hide forbidden books in their clothing, usually in their bodice or between their legs, with the result that inquisitorial searches can be considered a sort of symbolic violation of the female bodies that sought to protect those writings. Through such actions, Morisco women demonstrated an almost visceral relationship with written texts and created for themselves a crucial role as the guardians of Islamic tradition.